Implementasi Algortima Apriori dalam Sistem Informasi Penjualan Berbasis Web pada CV. Pahala Lima Waktu - Shatria Darma Putra Kustiana; Hendarman Lubis; Asep Ramdhani Mahbub (Journal of Informatic and Information Security, 2025)
The printing industry plays an important role in supporting promotional activities, communication, and various other business needs. However, at CV. Pahala Lima Waktu, the sales transaction recording process i s still performed manually using physical notes, leading to issues such as delayed data retrieval, input errors, and the absence of customer purchasing pattern analysis. To address these problems, this study designs a web-based sales information system equipped with data analysis features using the Apriori algorithm. This algorithm is one of the widely used Data Mining   techniques to discover associations between products through the calculation of support and confidence values. The system was developed using the Waterfall method, wi th PHP Native as the backend and MySQL as the database. The implementation results show that the system can digitize transaction processes, generate product association rules, and provide bundling recommendations that can be used as a company promotion strategy. With this integration, the system also functions as a Decision Support System (DSS) to assist staff in making promotion decisions based on historical sales data analysis.